2021
DOI: 10.1002/pri.1918
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the physical activity of stroke survivors in high‐income countries and low to middle‐income countries

Abstract: Background: Low physical activity levels in people with stroke may contribute to higher risk of cardiovascular disease morbidity and mortality. Differences in economic status, culture and the built environment may influence the applicability of interventions developed in high income countries (HIC) for stroke survivors in low to middle-income countries (LMIC).Purpose: To compare physical activity levels of stroke survivors in HIC and LMIC and to explore the influence of lower limb impairment on physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[ 14 ] Another study showed that high and medium levels of PA have beneficial effects on cardiovascular health, which can reduce the risk of stroke by 30% and 20% in men and women. [ 15 ] A study has shown that PA can improve cardiovascular adaptability, improve vascular elasticity, promote blood circulation, lower blood pressure and heart rate, and thus reduce the incidence of stroke. [ 16 ] A study shows that PA can reduce the inflammatory reaction in the body, which is closely related to atherosclerosis and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Another study showed that high and medium levels of PA have beneficial effects on cardiovascular health, which can reduce the risk of stroke by 30% and 20% in men and women. [ 15 ] A study has shown that PA can improve cardiovascular adaptability, improve vascular elasticity, promote blood circulation, lower blood pressure and heart rate, and thus reduce the incidence of stroke. [ 16 ] A study shows that PA can reduce the inflammatory reaction in the body, which is closely related to atherosclerosis and stroke.…”
Section: Introductionmentioning
confidence: 99%